Issues To Models: A Prescriptive Process for Substantive Architectural Form - Merrill C. Gaines (Oz, 1985)
As all of us who teach design know, the two-headed dilemma of the studio is to assist students in developing work that is both content laden as well as formally interesting. The best students manage this quite nicely on their own; most others have difficulty with one or the other, more often than not the latter...